Voltage Source Converter–Based Voltage Stiffness Compensator to Improve Grid Voltage Dynamics - Shang, Lei; Han, Chunyi; Dong, Xuzhu; Tian, Ye; Liu, Jianing (Frontiers in Energy Research, 2022)
This paper proposes a novel voltage source converter (VSC)-based voltage regulatory device based on energy storage and virtual synchronous control, called as static synchronous condenser (VSCON), to enhance grid voltage dynamics. In proposed VSCON, there is no inner cascaded current control and the output voltage of the VSC, i.e. inner potential, is directly connected to grid via a filter. Resilience characteristic is featured in inner potential of VSCON by the virtual synchronous control. On the basis of Resilience characteristic, the VSCON can naturally provide dynamic support for grid voltage. Compared to traditional synchronous condenser, the proposed VSCON is more flexible and contributes less short current. Compared to existing power electronic interfaced voltage regulatory device, the dynamic support is natural without any time delay and the proposed VSCON can improve the dynamic performance of grid voltage, which is helpful to alleviate the temporary over-voltage at sending terminal. Basic principle, control methods and application analysis are presented. Meanwhile a 10 kW prototype is set up and experiment results validate the feasibility and effectiveness of the proposed VSCON on improving grid voltage dynamics.